Effectiveness of Digital Transformation in Public Services in Bulukumba Regency - Rahman, Nawir (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Public services at the village level are a vital aspect in ensuring community welfare and participation in the development process. With the development of information and communication technology, villages have the opportunity to improve efficiency and service quality through innovation in public services. This study aims to analyze the effectiveness of digital transformation in public services through the Jaga Wargata Information System (SIJAWARA) in Bulukumba Regency, precisely in Bira Village, Bontobahari District. The research method used is qualitative with a case study approach. Data collection techniques such as observation, interviews, and documentation. While data analysis techniques use data triangulation, namely data reduction, data presentation, and closing. The results showed that the implementation of digital transformation in public services through SIJAWARA in Bira Village, Bulukumba Regency was effective, this can be seen from the indicators 1) transparency and accountability of services, namely the provision of information openly through the official website of Bira village; 2) community participation, namely public services carried out through the SIJAWARA application; 3) affordability and accessibility, namely all levels of society living in Bira village can easily reach and access SIJAWARA making it easier to provide services, and 4) quality of service, namely in addition to ease of access, SIJAWARA also provides fast service to the community.